The challenges of digital transformation, problems and promises : Case of Tunisian SMEs - Amine Ben Hadj Hassine (Quantitative Economics and Management Studies, 2022)
The objective of this article is to identify the challenges of Tunisian small and medium-sized enterprises (SMEs) in the implementation of Industry 4.0. Indeed, the Subject of Digital Transformation has its relevance as Industry 4.0 is considered as the first industrial revolution to be predicted before it happened. Competition from digital companies is disrupting business models, and leaders no longer have a choice: the time has come for digital transformation (Dussart, C, 2015). This transition is not new. It covers a necessary reality, especially for so-called traditional companies, which were not born in digital culture. Built on an old model, they must initiate and succeed in their transformation to remain competitive. This paper aims to analyze the opportunities brought by digital transformation for Tunisian companies. In our research and on the methodological section, we used an exploratory qualitative approach with Tunisian companies, using a questionnaire. The results of this investigation have shown that the great opportunities and challenges facing Tunisian companies are human capital in the first place, funding and above all methodological support. And the government must be the first to assist and support the digitization process.